Analysis of Tourism Promotion Strategies Through Twitter Social Media: A Case Study in Yogyakarta - Danang Kurniawan; Herpita Wahyuni; Arissy Jorgi Sutan (Journal of Local Government Issues (LOGOS), 2021)
Social media helps deliver information efficiently, Yogyakarta Government used social media to provide information on Yogyakarta’s tourism to society, mainly the local or foreign tourists. This research aims to see the strategy of delivering news of the City of Yogyakarta government to promote the tourism destination during the covid-19 pandemic transition period, using social media account @Jogja/Yogyakarta of City of Yogyakarta government in Twitter. This research used the qualitative approach with application-based used, or (Qualitative Data Analysis Software) the software used in this research is NVivo 12 plus.  In the part of the analysis used NVivo 12 Plus, begin with: (1) capture the data, (2) Import the information, (3) Coding the data, (4) Classification the data, and (5) Display the data.  This research shows that to promote tourism in Yogyakarta City applied with the integrated and consistent, after the Phenomena of Ciovid-19. Strategy to deliver the information focused on attracting the tourist to visit with applied the health protocol strictly, so that cerate the new culture that aims to reduce the spread of Covid-19, by limiting capacity, using Jogja Smart Service in monitoring the number of visitors.